Pengaruh Motivasi Kerja, Pelatihan Kepemimpinan dan Lingkungan Kerja Syariah terhadap Kinerja Pegawai di Kantor Pos Cabang Pacitan - Indrayani, Eka; Muhibbuddin, Muhammad Nur; Mahardika, Hanri Dhona; Hartono, Sri (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to analyze the influence of work motivation, leadership training, and sharia work environment on employee performance at the Pacitan Branch Post Office. In the world of work, factors such as motivation, training quality, and a supportive environment play a very important role in improving employee performance. The method used in this study is a quantitative approach with a survey as a data collection technique. The respondents in this study were employees at the Pacitan Branch Post Office totaling 41 people. The data obtained was analyzed using multiple linear regression techniques to determine the influence of each independent variable on employee performance. The results of the study show that work motivation, leadership training, and sharia work environment simultaneously have a positive effect on employee performance. Partially, work motivation and leadership training have a significant influence on performance improvement, while the sharia work environment, although it has a positive effect, is not significant. This research implies that companies need to focus more on developing work motivation and leadership training programs to improve employee performance, as well as create a more supportive work environment in accordance with sharia principles.